Hedonic Eating among Female Students: A Descriptive Study - Anggita Cahyani; Ari Setyorini; Wing Ispurwanto (Social Economics and Ecology International Journal (SEEIJ), 2018)
Obesogenic environment which characterized by a large number of cheap, easily accessible, delicious, and energy-dense foods has switch eating from energy need to pleasure. It raises the term hedonic hunger, or eats outside hunger and for pleasure. The aim of the study is to explore hedonic hunger in female students. Female students have been found as the more vulnerable when it comes about eating behaviour. N=211 in this study reported their hedonic hunger level using the Power of Food scale. The design of this study was quantitative descriptive. Data was analysed using descriptive technique. The result show that 37% participants were categorized as low in hedonic hunger, 37 % moderate, and 31.3% high. We conclude that this finding can be used as basis for healthy eating intervention that emphasizing the psychological aspect of eating.